Septic shock after spontaneous abortion in the 21st gestational week of pregnancy: a case report - Semczuk-Sikora, Anna; Krzyżanowski, Arkadiusz; Kwaśniewska, Anna (Menopause Review/Przegląd Menopauzalny, 2010)
Septic shock is a rare but dramatic complication in obstetrics with a high mortality rate. In the course of this condition, cardiovascular failure, severe hypotension and multiorgan dysfunction are observed. Usually, septic shock is also associated with disturbed coagulation. In our report, we present a case of septic shock caused by Escherichia coli after spontaneous abortion in the 21st gestational week of pregnancy in a 40-year-old woman. During intensive care, besides broad-spectrum antibiotics, hysterectomy was performed and activated protein C was administered. In our opinion, this treatment modality significantly improved the outcome in our patient.